Prevalence of Endometriosis in Postmenopausal Women: A Systematic Review - Ghinantia Athaya Putri; Emiliana Da Costa Margarida; Muhammad Faisal Azis (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Endometriosis is generally known as a condition that occurs in reproductive-age women, but cases in menopausal women have also been reported, especially in those who have received postmenopausal hormone therapy. The prevalence of endometriosis in menopausal women can reach 2.2% of all diagnosed cases of endometriosis. Material and Methods: There are 4 articles included from 3 databases. Several databases used included PubMed, ScienceDirect, and Taylor & Francis. The sample population included postmenopausal patients with endometriosis. Exclusion criteria included non-peer-reviewed journals, non-human research study designs, and grey literature. 4 articles are showing that endometriosis can occur in postmenopausal women. The articles show that the prevalence of endometriosis in postmenopausal women is around 2-20% where the diagnosis is made based on a combination of laparoscopic visualization and histological confirmation. Results: The occurrence of endometriosis in postmenopausal women can occur due to various risk factors, including the use of hormone replacement therapy (HRT) and obesity because it can increase estrogen levels, which results in the development of endometriosis. Therefore, it is important to recognize that endometriosis is not only limited to women of productive age but can also occur in those who have passed menopause because they are often suspected of being malignant. Conclusion: In general, patients with endometriosis have a higher risk of developing ovarian cancer. But, the clinical picture of endometriosis in menopausal patients is nonspecific. This makes endometriosis often experience a delay in diagnosis, especially in elderly patients. Postmenopausal women with endometriosis should be treated with surgery.